Potentials of optimized hybrid system in powering off-grid macro base transmitter station site - Anayochukwu, A.V.; Ndubueze, N.A. (International Journal of Renewable Energy Research, 2013)
This paper explores the possibility of hybridizing the diesel generator source system with renewable energy sources and demonstrates the potential of renewable energies to replace (partially) diesel as a source of power for mobile base station sites. The concept of hybridizing the diesel generator is to reduce both the operating cost and the quantity of different air pollutants. The patterns of load consumption by mobile base station are studied and suitably modeled for optimization using Hybrid Optimization Model for Electric Renewables (HOMER) software. The proposed Hybrid (Solar & Hydro) + DG system was simulated using the model which results in four different topologies. The solution with the highest optimization value is considered to be the best energy option (solution) for the Base Station Site. From the simulation results, the PV/Hydro-Diesel system solution has the highest optimization value. It saves $15,961,777 and 70.553 tonnes of CO2 when compared with diesel only.
Keywords: Base transmitter station (BTS); Diesel generator; HOMER; Hybrid System; Nigeria; Off-Grid site; Optimization; Power generation; Renewable energy; Simulation